2005
DOI: 10.1242/jcs.02291
|View full text |Cite
|
Sign up to set email alerts
|

DNA CpG hypomethylation induces heterochromatin reorganization involving the histone variant macroH2A

Abstract: In mammalian heterochromatin, cytosine bases of CpG dinucleotides are symmetrically modified by methylation. Patterns of CpG methylation are maintained by the action of Dnmt1, the mammalian maintenance cytosine methyltransferase enzyme. We genetically manipulated the levels of CpG methylation and found that extensive chromatin alterations occur in pericentric heterochromatin. Homozygous mutations in Dnmt1 cause severe hypomethylation of pericentric heterochromatin and concomitant chromatin reorganization invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 31 publications
1
35
0
4
Order By: Relevance
“…Eden et al have shown that DNA hypomethylation increased the rate of LOH in mouse embryonic fibroblasts (14). Recently, it has also been reported that DNA CpG hypomethylation induces a significant reorganization of constitutive pericentric heterochromatin (36). Our observation that LOH significantly correlated with global hypomethylation might be explained by the possibility that global hypomethylation may affect the molecular composition of heterochromatin and chromatin conformation, and may promote LOH by destabilizing the genome.…”
Section: Discussionsupporting
confidence: 58%
“…Eden et al have shown that DNA hypomethylation increased the rate of LOH in mouse embryonic fibroblasts (14). Recently, it has also been reported that DNA CpG hypomethylation induces a significant reorganization of constitutive pericentric heterochromatin (36). Our observation that LOH significantly correlated with global hypomethylation might be explained by the possibility that global hypomethylation may affect the molecular composition of heterochromatin and chromatin conformation, and may promote LOH by destabilizing the genome.…”
Section: Discussionsupporting
confidence: 58%
“…Rather than being structurally static as first believed, it is becoming clear that these large highly compacted domains are dynamic since their protein composition can change during cellular differentiation (10,26,50), between transitions from proliferation to quiescence (21), and when the levels of CpG methylation are altered (37). This argues that the function(s) of constitutive heterochromatin may vary with the cellular context.…”
mentioning
confidence: 99%
“…However, it is possible that some unrecognized changes in heterochromatin occur in TKO cells. Indeed, the redistribution of the histone variant macroH2A into pericentromeric heterochromatin in hypomethylated Dnmt1 -/-ES cells has recently been reported (Ma et al 2005), indicating that CpG methylation modulates some properties of heterochromatic domains. Although the apparent contribution of CpG methylation to the steady-state heterochromatin structure in ES cells may be small, it is possible that CpG methylation might serve as a mark for anchoring heterochromatin during dynamic chromatin remodeling or during multiple replication processes.…”
Section: Discussionmentioning
confidence: 99%